Librarian Copyright Literacy: Self-Reported Copyright Knowledge Among Information Professionals in the United States. Issue 3 (2nd July 2016) - Estell, Allison; Saunders, Laura
Abstract : Librarians often act as default copyright experts at their institutions and thus must have an awareness of copyright law and practices. Nevertheless, there is little in the scholarly literature about how well informed librarians are about copyright law. Through a national survey of professional librarians, this study illustrates librarians' self-perceived familiarity with copyright concepts, interests in training, and sources of support for copyright questions. The results will be of interest to library directors and library and information science (LIS) faculty and could inform curricular decisions in LIS schools and may also be applied to local professional development initiatives for librarians.